COVID-19 a działalność przedsiębiorcza: analiza porównawcza konsekwencji i oczekiwań - Avdeenko, Galina; Dmitrev , Sergey; Zieliński, Jacek (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2020)
The article presents the results of a sociological survey conducted in five regions of Russia in May 2020 regarding the consequences of the SARS CoV-19 pandemic and the resulting restrictive measures on regional entrepreneurial activity. As the results of the study show, these consequences are extremely negative: the respondents of the survey claim significant losses for their business, some claim that the business is completely destroyed. The article compares the expectations of Russian businessmen regarding the timing and pace of overcoming the crisis caused by quarantine measures with the results of studies conducted by Boston consulting group and McKinsey. It can be argued that among the international, as well as the Russian business community, there is a certain similarity of expectations regarding the length of recovery from the crisis. One of the important aspects of the article is the study of the role of expert community in the development of anti-crisis measures in the field of economics.